Haiti Unbound : A Spiralist Challenge to the Postcolonial Canon - Glover, Kaiama L., 1972- (Book collections on Project MUSE., 2010)
"Historically and contemporarily, politically and literarily, Haiti has long been relegated to the margins of the so-called 'New World'. Marked by exceptionalism, the voices of some of its most important writers have consequently been muted by the geopolitical realities of the nation's fraught history. This book offers a close look at the works of three such writers: the Haitian Spiralists Franketienne, Jean-Claude Fignole, and Rene Philoctete. While Spiralism has been acknowledged by scholars and regional writer-intellectuals, the Spiralist ethic-aesthetic not yet been given the sustained attention of a full-length study. This book attempts to consider the works of the three Spiralist authors both individually and collectively. This book engages with long-standing issues of imperialism and resistance culture in the transatlantic world. It emphatically articulates Haiti's regional and global centrality, combining vital 'big picture' reflections on the field of postcolonial studies with elegant close-reading-based analyses of the philosophical perspective and creative practice of a distinctively Haitian literary phenomenon."--Publisher's description